Carbon and Beyond: The Biogeochemistry of Climate in a Rapidly Changing Amazon - Covey, Kristofer; Soper, Fiona; Pangala, Sunitha; Bernardino, Angelo; Pagliaro, Zoe; Basso, Luana; Cassol, Henrique; Fearnside, Philip; Navarrete, Diego; Novoa, Sidney; Sawakuchi, Henrique; Lovejoy, Thomas; et al. (Frontiers in Forests and Global Change, 2021)
The Amazon Basin is at the center of an intensifying conversation about deforestation, land-use, and global change. To date, climate research in the Basin has overwhelmingly focused on the cycling and storage of carbon (C) and its implications for global climate. Missing, however, is more comprehensive consideration of other significant climate forcing agents (i.e., CH4, N2O, black carbon, biogenic volatile organic compounds, BVOCs, transpiration, and albedo) and their dynamic responses to both localized (fire, land use change and management, infrastructure development, storms) and global (warming, drying) change. Here, we synthesize the current understanding of 1) sources and fluxes of all major forcing agents, 2) the demonstrated or expected impact of global and local changes on each agent, and 3) the nature, extent, and drivers of anthropogenic change in the Basin. We highlight large uncertainty in flux magnitude and responses, and their corresponding direct and indirect effects on the regional and global climate system. Despite uncertainty in their responses to change, we conclude that current warming from non-CO2 agents (especially CH4 and NO2) in the Amazon Basin largely offsets — and most likely exceeds — the climate service provided by atmospheric CO2 uptake. We also find that the majority of anthropogenic impacts act to increase the radiative forcing potential of the Basin. Given the large contribution of less-recognized agents (e.g. Amazonian trees alone emit ~3.5% of all global CH4), a continuing focus on a single metric (i.e., C uptake and storage) is incompatible with genuine efforts to understand and manage the biogeochemistry of climate in a rapidly changing Amazon Basin.